1994
DOI: 10.1128/jvi.68.12.7738-7745.1994
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the capsid protein of Leishmania RNA virus LRV1-4

Abstract: The virion of Leishmania RNA virus is predicted to be composed of a 742-amino-acid major capsid protein and a small percentage of capsid-polymerase fusion molecules. Recently, the capsid protein alone was expressed and shown to spontaneously assemble into viruslike particles. Since the major structural protein of the virion shell self-assembles into viruslike particles when expressed in the baculovirus expression system, assembly of the virion can be studied by mutational analysis and expression of a single op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The finding that the CP N-terminal deletion CP-N71 which lacked 71 amino acid residues was incapable of portant in the packaging of the RNA-dependent RNA polymerase (RDRP) and viral genome into Hv190SV cap-assembly was not surprising in view of the results of a similar study with the totivirus LRV1-4 (Cadd et al, 1994). sids as has been reported for some other viruses (Lazinski and Taylor, 1993).…”
Section: Assembly Of Expressed P78 and P88 Into Virus-like Particlesmentioning
confidence: 57%
“…The finding that the CP N-terminal deletion CP-N71 which lacked 71 amino acid residues was incapable of portant in the packaging of the RNA-dependent RNA polymerase (RDRP) and viral genome into Hv190SV cap-assembly was not surprising in view of the results of a similar study with the totivirus LRV1-4 (Cadd et al, 1994). sids as has been reported for some other viruses (Lazinski and Taylor, 1993).…”
Section: Assembly Of Expressed P78 and P88 Into Virus-like Particlesmentioning
confidence: 57%
“…Both LR1 and LR2 were thought to contain single-stranded DNA [ 8 ], but soon after, they were demonstrated to contain circular double-stranded RNAs (dsRNAs) and were renamed Leishmania RNA virus (LRV) [ 9 ]. In the following years, LRV was described in 12 isolates of L. braziliensis and L. guyanensis from the Amazon region [ 10 ], and LRV was identified in one Leishmania ( Leishmania ) major isolate from a human patient in the former Soviet Union [ 11 ]. To the best of our knowledge, there are no studies that have searched for viruses in L .…”
Section: Introductionmentioning
confidence: 99%
“…Viruses found in some strains of the protozoan parasite Leishmania consist of spherical capsids containing a dsRNA genome of -5280 nucleotides (nt) (1-3). The two overlapping open reading frames, ORF2 and ORF3, encode the 82 kDa capsid protein (4) and the RNA-dependent RNA polymerase (RDRP) (5), respectively. A comparison of the LRV1 RDRP sequence with homologous sequences from other viruses (5) showed that the yeast L-A/ScV virus RDRP gene is the sequence most similar to LRV.…”
Section: Introductionmentioning
confidence: 99%